Policy innovation of construction waste management in Xi’an, China: A SWOT analysis of incentive mechanisms - Han Liu; Siqing Yang; Muhammad Noor Hisyam Jusoh (PLoS ONE, 2025)
This study uses Xi’an as a case to explore incentive mechanisms and optimization pathways in construction waste management. Drawing on policy text analysis, semi-structured interviews, and the Delphi method, and employing the SWOT-TOWS framework, the research systematically evaluates the strengths, weaknesses, opportunities, and threats of current policies. The findings indicate that while Xi’an benefits from fiscal support and standard-setting, inefficiencies in policy enforcement and low market trust continue to hinder effective resource utilization. To address these challenges, the study proposes a phased strategy: in the short term, improve regulatory closure and enforcement mechanisms; in the medium term, strengthen capacity building, establish market-supporting measures, and stabilize demand; and in the long term, promote institutionalization, financial diversification, and large-scale development. Such measures aim to facilitate the transition from “policy-driven pilot projects” to “market-driven normalization.” This study provides practical insights for Xi’an and other cities at a similar stage of development in building more comprehensive policy support frameworks for sustainable construction waste management.